Carbon nanomaterial, composite sheet molding compound based on carbon nanomaterial and preparation method of composite sheet molding compound

Through the composite of nanocarbon materials and sheet molding materials, the problem of insufficient mechanical properties of existing sheet molding materials is solved, and the strength and toughness of the materials are significantly improved, which is suitable for products of automotive exterior parts.

CN119570112APending Publication Date: 2025-03-07SHAANXI COAL & CHEM TECH INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411941342.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The mechanical properties of existing sheet molding materials are insufficient and cannot meet the high requirements for product strength of automotive exterior parts.

Method used

Nanocarbon material is used as filler and flake molding material, and nanocarbon material with high specific surface area is obtained by reacting graphite powder with concentrated acid intercalation, hydrogen peroxide expansion, crushing and microwave expansion treatment, and its compatibility is enhanced by silane modification treatment.

Benefits of technology

The tensile strength, bending strength and impact strength of the composite material have been significantly improved, and the tensile strength, flexural strength and impact strength are enhanced by more than 30-40%, 45-60%, and 35-50%, respectively, making up for the disadvantages of poor toughness and low strength of sheet molding materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570112A_ABST
    Figure CN119570112A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanomaterial, a composite sheet molding compound based on the carbon nanomaterial and a preparation method of the composite sheet molding compound, and belongs to the technical field of sheet molding compounds. According to the preparation method disclosed by the invention, graphite powder and concentrated acid are subjected to intercalation reaction, hydrogen peroxide puffing is carried out, so that the spacing of graphite layers is increased, and then crushing and microwave puffing treatment are carried out, so that the nano carbon material with a relatively large specific surface area is obtained; finally, through modification treatment of silane, the compatibility of the nanocarbon and unsaturated resin as an SMC raw material is enhanced; and the nano carbon material with high specific surface area is fully and uniformly dispersed in the resin matrix to play a supporting role, so that the mechanical strength of the material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sheet molding compounds, and in particular relates to a nano-carbon material and a composite sheet molding compound based thereon and a preparation method thereof. Background Art

[0002] As a typical thermosetting composite material, the preparation process of sheet molding compound (SMC) embodies the perfect combination of material science and engineering technology. In the preparation process, unsaturated polyester resin is first used as the base material, followed by the addition of inorganic fillers to improve physical properties, curing agents to ensure that the material can be stably cured under specific conditions, and thickeners to adjust the viscosity of the resin paste to make it easier to process. In addition, other additives may be added as needed to further improve the comprehensive performance of the material. In order to enhance the mechanical properties and durability of the material, short-cut glass fibers are also added to the resin paste. These fibers build a strong support network in the material like steel bars. The reason why SMC can be widely used in the field of automotive materials is due to its simple and efficient production process, highly automated production process, relatively low cost and excellent mechanical strength. More importantly, it can easily form various complex components to meet the multiple requirements of automotive design for lightweight, high strength and complex shapes. Therefore, SMC materials play a pivotal role in the automotive manufacturing industry and are one of the key factors in promoting lightweight vehicles and improving vehicle performance.

[0003] Although sheet molding compounds have many advantages, due to the complexity of their preparation process, they also have problems such as cracking, blistering, insufficient mechanical strength, and surface defects. As automotive exterior parts have higher and higher requirements for product strength, the performance of existing sheet molding compounds has gradually failed to meet the use requirements. Summary of the invention

[0004] The object of the present invention is to provide a nano-carbon material and a composite sheet molding compound based thereon and a preparation method thereof, so as to solve the technical problem that the existing sheet molding compound has poor mechanical properties.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a nano carbon material, comprising the following steps: After mixing graphite powder and concentrated acid, hydrogen peroxide is added to react, and after the reaction is completed, the obtained reaction product is post-treated to obtain a filter cake; After drying the filter cake, an intermediate product powder A is obtained; The intermediate product powder A is subjected to microwave reduction to obtain an intermediate carbon material; The intermediate carbon material is crushed and modified in sequence to obtain a nano carbon material.

[0006] Furthermore, the mass ratio of the graphite powder to the concentrated acid is 1:(20-80); the mass ratio of the graphite powder to hydrogen peroxide is 1:(0.5-5).

[0007] Further, the graphite powder is mixed with concentrated acid for 1-3 hours, the temperature is maintained at 10-15° C., and hydrogen peroxide is added at a stirring speed of 500-1200 rpm, and the mixture is stirred for reaction for 1-3 hours; The mass concentration of the hydrogen peroxide is 30%.

[0008] Furthermore, the graphite powder is one of expandable graphite powder and flake graphite powder; the concentrated acid is one of concentrated sulfuric acid, a mixture of concentrated sulfuric acid and concentrated nitric acid, and a mixture of concentrated sulfuric acid and concentrated phosphoric acid.

[0009] Furthermore, the post-treatment includes washing and centrifugation performed in sequence; the washing is ultrasonic washing with deionized water for 5-10 times until the pH value of the supernatant is between 5.5-7.5.

[0010] Furthermore, the drying method is spray drying; the temperature of the spray drying is 200-300°C; The microwave reduction is to use nitrogen to continuously blow the intermediate product powder A into a microwave puffing furnace at 800-1200°C for microwave reduction; The pulverizing method is air flow pulverizing; the fan frequency used in the air flow pulverizing is 40-60 Hz.

[0011] Furthermore, the modification process comprises: The pulverized intermediate carbon material is configured into a nanocarbon aqueous solution, a silane coupling agent is added, and the mixture is stirred and reacted under oil bath heating conditions, followed by centrifugal drying to obtain a nanocarbon material.

[0012] Furthermore, the silane coupling agent is KH550; the mass concentration of the nanocarbon aqueous solution is 5%-8%; the mass percentage of the silane coupling agent in the nanocarbon aqueous solution is 1%-5%; the temperature of the oil bath heating is 60-80°C; and the reaction is stirred for 2-5 hours under the oil bath heating conditions.

[0013] The present invention also discloses a nano carbon material prepared by the above method, wherein the specific surface area of ​​the nano carbon material is 300-1000 m 2 / g, D50 is 20-80 μm.

[0014] The invention also discloses a composite sheet molding compound prepared by using the nano carbon material as filler and compounding it with a sheet molding compound.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a nano-carbon material. Graphite powder and concentrated acid are intercalated and expanded by hydrogen peroxide to increase the distance between graphite layers. Then, the nano-carbon material with a large specific surface area is obtained by crushing and microwave expansion. Finally, the nano-carbon material is modified by silane to enhance the compatibility of the nano-carbon with an unsaturated resin as a raw material of SMC. The nano-carbon material with a high specific surface area is fully and evenly dispersed in a resin matrix to play a supporting role, thereby enhancing the mechanical strength of the material.

[0016] The present invention also discloses a composite sheet molding compound, which is prepared by using the above-mentioned nano-carbon material as a filler and composited with the sheet molding compound, and can greatly improve the tensile strength, impact strength and flexural strength of the material, achieving the performance target of high strength of the material. Relevant experimental results have proved that compared with ordinary sheet molding compounds, the tensile strength, flexural strength and impact strength of the composite sheet molding compound of the present invention are respectively enhanced by 30-40%, 45-60% and 35-50% or more, which perfectly makes up for the shortcomings of poor toughness and low strength of the sheet molding compound. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The figure is a flow chart for preparing the nano-carbon material of the present invention. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0023] like Figure 1 As shown, the present invention provides a method for preparing a nano-carbon material, comprising the following steps: Step 1: Oxidation reaction stage The graphite powder and concentrated acid are fully mixed, and then hydrogen peroxide is added and stirred for reaction. After the reaction is completed, a reaction product is obtained; Step 2: Ultrasonic cleaning stage The obtained reaction product is ultrasonically washed several times in deionized water, and the washed product is centrifuged to obtain a filter cake; Step 3: Spray drying stage The filter cake is spray dried to obtain an intermediate product powder A; Step 4: Microwave reduction stage The intermediate product powder A is subjected to microwave reduction to obtain an intermediate carbon material; Step 5: Airflow crushing stage pulverizing the intermediate carbon material in a jet mill; Step 6: Powder modification stage A silane coupling agent is added to the pulverized intermediate carbon material for modification to obtain a high-strength nano-carbon material dedicated to sheet molding compounds.

[0024] Preferably, in step 1, the graphite powder is one of expandable graphite and 325-12000 mesh flake graphite, the concentrated acid is one of concentrated sulfuric acid, a mixture of concentrated sulfuric acid and concentrated nitric acid, and a mixture of concentrated sulfuric acid and concentrated phosphoric acid, and the mass ratio of graphite powder to concentrated acid is 1:20-80; the graphite powder and concentrated acid are stirred and mixed for 1-3 h, and the temperature of the system is maintained at 10-15 ° C; after adding hydrogen peroxide, the reaction is stirred and reacted for 1-3 h.

[0025] Preferably, in step 1, the hydrogen peroxide used is commercially available 30% H2O2, the mass ratio of graphite powder to hydrogen peroxide is 1:0.5-5, and the stirring speed is 500-1200 rpm.

[0026] Preferably, in step 2, deionized water is used 5-10 times to make the pH of the supernatant liquid between 5.5-7.5.

[0027] Preferably, in step 3, the spray drying temperature is 200-300° C., and the dried material is collected after continuous feeding for several minutes.

[0028] Preferably, in step 4, powder A is continuously blown into a microwave puffing furnace at 800-1200° C. with nitrogen for reduction, and the nano-carbon powder is collected with a cloth bag.

[0029] Preferably, in step 5, the fan frequency of the air flow mill is 40-60 Hz.

[0030] Preferably, in step 6, the silane coupling agent is KH550, a 5-8% nanocarbon aqueous solution is prepared and 1-5% of the silane coupling agent is added, the mixture is stirred and reacted for 2-5 h under 60-80°C oil bath heating conditions, and centrifuged and dried to obtain a nanocarbon material for high-strength sheet molding compound.

[0031] The present invention also discloses a nano carbon material prepared by the above preparation method, wherein the specific surface area of ​​the prepared nano carbon is 300-1000 m 2 / g, D50 is 20-80 μm.

[0032] The prepared nano-carbon is used as a filler and compounded with a sheet molding compound to obtain a composite material, and the tensile strength, bending strength and impact strength of the composite material are respectively enhanced by more than 30-40%, 45-60% and 35-50%.

[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0034] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0035] Example 1 A method for preparing a nano-carbon material comprises the following steps: Add 325 mesh flake graphite and concentrated sulfuric acid in a mass ratio of 1:20 into the reactor, introduce circulating cooling water, and stir at 1000 rpm for 3 h at a temperature of 10°C to evenly disperse the flake graphite in the concentrated sulfuric acid to form a uniform viscous black solution; keep the system temperature and speed unchanged, slowly add hydrogen peroxide to the solution, where the mass ratio of hydrogen peroxide to flake graphite is 1:1, and continue the reaction for 2 h; The reaction was terminated, and the product after the reaction was collected. The product was washed three times with deionized water to test the pH of the supernatant to be about 5.5, and the filter cake was obtained by centrifugation; The obtained filter cake was dried at 240°C in a spray drying tower to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 900°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 40 Hz; Subsequently, a 5% nanocarbon aqueous solution was prepared and a 1% silane coupling agent was added. The mixture was stirred and reacted for 2 h in an oil bath at 60 °C. After centrifugation, the mixture was dried at 60 °C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0036] The nano-carbon powder prepared in this example was added as a filler into a sheet molding compound. After testing, the tensile strength, flexural strength and impact strength of the prepared composite material were increased by 32%, 46% and 38% respectively.

[0037] Example 2 A method for preparing a nano-carbon material comprises the following steps: Add a mixed acid of expandable graphite and concentrated sulfuric acid and nitric acid in a mass ratio of 1:50 into the reactor, introduce circulating cooling water, and stir at a speed of 1500 rpm for 2 h at a temperature of 15 °C to evenly disperse the expandable graphite in the concentrated sulfuric acid to form a uniform and viscous black solution; keep the temperature and speed of the system unchanged, slowly add hydrogen peroxide to the solution, wherein the mass ratio of hydrogen peroxide to expandable graphite is 2:1, and continue the reaction for 2 h; The reaction was terminated, and the product after the reaction was collected. The product was washed with deionized water four times to test the pH of the supernatant to be about 6.0, and the filter cake was obtained by centrifugation; The obtained filter cake was dried at 260°C in a spray drying tower to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 1000°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 50 Hz; Subsequently, an 8% nanocarbon aqueous solution was prepared and a 2% silane coupling agent was added. The mixture was stirred and reacted for 5 h in an 80°C oil bath. After centrifugation, the mixture was dried at 80°C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0038] The nano-carbon powder prepared in this example was added as a filler into a sheet molding compound. After testing, the tensile strength, flexural strength and impact strength of the prepared composite material were increased by 35%, 50% and 42% respectively.

[0039] Example 3 A method for preparing a nano-carbon material comprises the following steps: Add expandable graphite and a mixed acid of concentrated sulfuric acid, concentrated nitric acid and concentrated phosphoric acid in a mass ratio of 1:80 into the reactor, introduce circulating cooling water, and stir at 2000 rpm for 3 h at a temperature of 15 °C. The expandable graphite is evenly dispersed in the concentrated sulfuric acid to form a uniform and viscous black solution. Keep the system temperature and speed unchanged, slowly add hydrogen peroxide to the solution, wherein the mass ratio of hydrogen peroxide to expandable graphite is 0.5:1, and continue the reaction for 3 h. The reaction was terminated, and the product after the reaction was collected. The product was washed four times with deionized water to test the pH of the supernatant to be about 6.5, and the filter cake was obtained by centrifugation; The obtained filter cake was dried at 220°C in a spray drying tower to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 1200°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 50 Hz; Subsequently, a 10% nanocarbon aqueous solution was prepared and a 5% silane coupling agent was added. The mixture was stirred and reacted for 4 h in an oil bath at 70 °C. After centrifugation, the mixture was dried at 70 °C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0040] The nano-carbon powder prepared in this example was added as a filler into a sheet molding compound. After testing, the tensile strength, flexural strength and impact strength of the prepared composite material were increased by 38%, 54% and 45% respectively.

[0041] Example 4 A method for preparing a nano-carbon material comprises the following steps: Add a mixture of expandable graphite powder and concentrated sulfuric acid and concentrated nitric acid in a mass ratio of 1:80 into the reactor, introduce circulating cooling water, and stir at 500 rpm for 3 h at a temperature of 15 °C to evenly disperse the expandable graphite powder in the mixture of concentrated sulfuric acid and concentrated nitric acid to form a uniform and viscous black solution; keep the system temperature and speed unchanged, slowly add hydrogen peroxide to the solution, wherein the mass ratio of hydrogen peroxide to expandable graphite powder is 1:5, and continue the reaction for 3 h; The reaction was terminated, and the product after the reaction was collected. The product was ultrasonically washed 5 times with deionized water, and the pH of the supernatant was tested three times to be about 7.5, and the filter cake was obtained by centrifugation; The obtained filter cake was dried in a spray drying tower at 200°C to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 1200°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 60 Hz; Subsequently, an 8% nanocarbon aqueous solution was prepared and a 1% silane coupling agent was added. The mixture was stirred and reacted for 5 h in an 80°C oil bath. After centrifugation, the mixture was dried at 60°C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0042] Example 5 A method for preparing a nano-carbon material comprises the following steps: Add a mixture of expandable graphite powder and concentrated sulfuric acid and concentrated phosphoric acid in a mass ratio of 1:40 into the reactor, introduce circulating cooling water, and stir at a temperature of 13 °C and a speed of 1200 rpm for 1 h to evenly disperse the expandable graphite powder in the mixture of concentrated sulfuric acid and concentrated phosphoric acid to form a uniform and viscous black solution; keep the system temperature and speed unchanged, slowly add hydrogen peroxide to the solution, wherein the mass ratio of hydrogen peroxide to expandable graphite powder is 1:0.5, and continue the reaction for 2 h; The reaction was terminated, and the product after the reaction was collected. The product was ultrasonically washed 10 times with deionized water, and the pH of the supernatant was tested three times to be about 6, and the filter cake was obtained by centrifugation; The obtained filter cake was dried at 250°C in a spray drying tower to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 800°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 50 Hz; Subsequently, a 5% nanocarbon aqueous solution was prepared and a 5% silane coupling agent was added. The mixture was stirred and reacted for 3 h in an oil bath at 70 °C. After centrifugation, the mixture was dried at 60 °C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0043] Example 6 A method for preparing a nano-carbon material comprises the following steps: Add a mixture of flake graphite powder and concentrated sulfuric acid and concentrated phosphoric acid in a mass ratio of 1:70 into the reactor, introduce circulating cooling water, and stir at 650 rpm for 1 h at a temperature of 10 °C to evenly disperse the flake graphite powder in the mixture of concentrated sulfuric acid and concentrated phosphoric acid to form a uniform and viscous black solution; keep the system temperature and speed unchanged, slowly add hydrogen peroxide to the solution, wherein the mass ratio of hydrogen peroxide to flake graphite powder is 1:3, and continue the reaction for 2 h; The reaction was terminated, and the product after the reaction was collected. The product was ultrasonically washed 10 times with deionized water, and the pH of the supernatant was tested three times to be about 6, and the filter cake was obtained by centrifugation; The obtained filter cake was dried at 250°C in a spray drying tower to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 800°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 50 Hz; Subsequently, a 5% nanocarbon aqueous solution was prepared and a 5% silane coupling agent was added. The mixture was stirred and reacted for 3 h in an oil bath at 70 °C. After centrifugation, the mixture was dried at 60 °C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0044] Example 7 A method for preparing a nano-carbon material comprises the following steps: Add a mixture of flake graphite powder and concentrated sulfuric acid and concentrated phosphoric acid in a mass ratio of 1:55 into the reactor, introduce circulating cooling water, and stir at 1100 rpm at 15 °C for 1 h to evenly disperse the flake graphite powder in the mixture of concentrated sulfuric acid and concentrated phosphoric acid to form a uniform viscous black solution; keep the system temperature and speed unchanged, slowly add hydrogen peroxide to the solution, where the mass ratio of hydrogen peroxide to flake graphite powder is 1:3, and continue the reaction for 2 h; The reaction was terminated, and the product after the reaction was collected. The product was ultrasonically washed 10 times with deionized water, and the pH of the supernatant was tested three times to be about 6, and the filter cake was obtained by centrifugation; The obtained filter cake was dried at 250°C in a spray drying tower to obtain an intermediate product powder A; The intermediate product powder A is blown into a microwave expansion furnace with nitrogen and reduced at a high temperature of 950°C to obtain an intermediate carbon material; The intermediate carbon material is passed into a jet mill to pulverize the powder at a frequency of 60 Hz; Subsequently, a 5% nanocarbon aqueous solution was prepared and a 5% silane coupling agent was added. The mixture was stirred and reacted for 3 h in an oil bath at 70 °C. After centrifugation, the mixture was dried at 60 °C to obtain a nanocarbon material specifically for high-strength sheet molding compounds.

[0045] Taking ordinary sheet molding compound as a blank sample, the performance of the blank sample and the composite sheet molding compound obtained in Example 1 to Example 3 were compared to obtain the data in Table 1. It can be seen from Table 1 that after adding the nano-carbon material, the tensile strength, flexural strength and impact strength of the composite material sample are greatly improved, indicating that the addition of the nano-carbon material has a good effect of mechanical enhancement, and can be used as a reinforcing additive for sheet molding compound, which has broad industrial prospects and market.

[0046] Table 1. Mechanical properties of blank samples and composite samples

[0047] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a nano-carbon material, characterized in that: The following steps are involved: After mixing graphite powder and concentrated acid, hydrogen peroxide is added to react, and after the reaction is completed, the obtained reaction product is post-treated to obtain a filter cake; After drying the filter cake, an intermediate product powder A is obtained; The intermediate product powder A is subjected to microwave reduction to obtain an intermediate carbon material; The intermediate carbon material is crushed and modified in sequence to obtain a nano carbon material.

2. The method for preparing a nano-carbon material according to claim 1, characterized in that: The mass ratio of the graphite powder to the concentrated acid is 1:(20-80); the mass ratio of the graphite powder to hydrogen peroxide is 1:(0.5-5).

3. The method for preparing a nano-carbon material according to claim 1, characterized in that: The graphite powder is mixed with concentrated acid for 1-3 hours, the temperature is maintained at 10-15°C, hydrogen peroxide is added, and the mixture is stirred at a stirring speed of 500-1200 rpm for 1-3 hours; The mass concentration of the hydrogen peroxide is 30%.

4. The method for preparing a nano-carbon material according to claim 1, characterized in that: The graphite powder is one of expandable graphite powder and flake graphite powder; the concentrated acid is one of concentrated sulfuric acid, a mixture of concentrated sulfuric acid and concentrated nitric acid, and a mixture of concentrated sulfuric acid and concentrated phosphoric acid.

5. The method for preparing a nano-carbon material according to claim 1, characterized in that: The post-treatment includes washing and centrifugation in sequence; the washing is ultrasonic washing with deionized water for 5-10 times until the pH value of the supernatant is between 5.5-7.

5.

6. The method for preparing a nano-carbon material according to claim 1, characterized in that: The drying method is spray drying; the temperature of the spray drying is 200-300°C; The microwave reduction is to use nitrogen to continuously blow the intermediate product powder A into a microwave puffing furnace at 800-1200°C for microwave reduction; The pulverizing method is air flow pulverizing; the fan frequency used in the air flow pulverizing is 40-60 Hz.

7. The method for preparing a nano-carbon material according to claim 1, characterized in that: The steps of the modification treatment are: The pulverized intermediate carbon material is configured into a nanocarbon aqueous solution, a silane coupling agent is added, and the mixture is stirred and reacted under oil bath heating conditions, followed by centrifugal drying to obtain a nanocarbon material.

8. The method for preparing a nano-carbon material according to claim 7, characterized in that: The silane coupling agent is KH550; the mass concentration of the nanocarbon aqueous solution is 5%-8%; the mass percentage of the silane coupling agent in the nanocarbon aqueous solution is 1%-5%; the temperature of the oil bath heating is 60-80°C; the reaction is stirred for 2-5 hours under the oil bath heating conditions.

9. The nanocarbon material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The specific surface area of ​​the nanocarbon material is 300-1000 m 2 / g, D50 is 20-80 μm.

10. A composite sheet molding compound, characterized in that: The nano carbon material according to claim 9 is used as a filler and is compounded with a sheet molding compound to obtain the composite.